Paham Misi Katolik dari Sudut Pandang Mahasiswa-Mahasiswi Diaspora Manggarai di Kota Malang, Jawa Timur - Jegaut, Siprianus; Kristiyani, Ameilia Magdalena (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2023)
The focus of this study is to discuss “Understanding Catholic Mission from the Perspective of Manggarai Diaspora Students in Malang City, East Java. ”Mission work is a public duty and an obligation for all those who have been baptized. However, many people who have been baptized see missionary work as the sole responsibility of bishops, priests, nuns, brothers or nuns.This mindset makes other people feel they are not participating in carrying out the task, so they ignore it. Manggarai diaspora students are aware of their presence in a pluralistic society as a representation of the presence of the Church. They are present not only seeking knowledge, but also trying to be witnesses of Christ in their own style and way. This study has the objective of how far the Manggarai diaspora students have realized the work of mission in the midst of a pluralistic society in the city of Malang. The methodology used is phenomenology from the reality of the daily experiences of Manggarai diaspora students. This study found, first, the students had taken part in mission work in their own way. Second, we need to have skills about the local culture. Third, adaptation to the local context